HIV care in Istanbul, Turkey: How far is it from the UNAIDS 90–90–90 targets?. (November 2019) - Mete, Bilgul; Gunduz, Alper; Bolukcu, Sibel; Karaosmanoglu, Hayat K; Yildiz, Dilek; Koç, Meliha M; Aydın, Ozlem A; Dokmetas, Ilyas; Tabak, Fehmi
The prevalence of human immunodeficiency virus (HIV) infection is low but it is steadily increasing in Turkey. In the current study, we aimed to assess the status of HIV infection management with the proposed 90–90–90 targets in a large HIV cohort in Istanbul, Turkey. The cohort included 2382 patients (2082 male, 300 female, mean age was 36.3 ± 11.3 years). Mean CD4 cell count was 399 cells/mm 3 and HIV-RNA level was 576, 235 copies/ml. According to the modeling by the Modeling tool of European Center for Diseases Control Software, 72 and 74% of all HIV patients had been diagnosed in 2016 and 2017, respectively (the first target). Among 2382 patients, 2191 (92%) were on antiretroviral therapy (the second target). The third target of virally suppressing those on treatment was achieved among 70.2% of the patients. The current study suggests that both the fraction of those living with undiagnosed HIV and the proportion of those on treatment who are virally suppressed should be targeted to sustain optimal HIV care. Efforts should continue to surpass the targets of 90–90–90.